Effect of eprosartan on the hemostatic system in patients with chronic kidney disease associated with hereditary thrombophilia - Kaliuzhin, V V; Sibireva, O F; Urazova, O I; Tkalich, L M; Zibnitskaia, L I; Kaliuzhina, E V; Sazonov, É A; Grankina, V Iu (Terapevtic̆eskii arhiv, 2013)
To study the effect of eprosartan, an angiotensin II type 1 (AT1) receptor blocker, with sympatholytic activity on the hemostatic system in patients with chronic kidney disease (CKD) associated with hereditary thrombophilia. The 12-week open-label uncontrolled trial included 31 patients with Stages I-II CKD: 15 patients with chronic glomerulonephritis and 16 with diabetic nephropathy burdening types 1 and 2 diabetes mellitus (DM) in 10 and 6 cases, respectively. In all the patients, CKD was associated with one of the heterozygous forms of thrombophilia: the polymorphic methylenetetrahydrofolate reductase gene variant C677T was found in 18 patients; the polymorphic coagulation factor V gene variant G1691A was in 9; and the polymorphic coagulation factor II gene variant G20210A in 4. Along with the thorough examination accepted in nephrology and endocrinology clinics, investigations of vascular-thrombocytic and secondary hemostasis and the anticoagulant and fibrinolytic systems were made before and after treatment. Eprosartan therapy caused positive changes in the indicators of vascular-thrombocytic (diminished platelet aggregation, reduced surplus of von Willebrand factor and endothelin-1) and secondary (decreased coagulation factor VII activity, longer activated partial thromboplastin time) hemostasis and the anticoagulant (reduced antithrombin III deficiency) and fibrinolytic (elevated blood plasminogen concentrations) systems. The pleiotropic effects of eprosartan may be used to correct hypercoagulability syndrome in patients with CKD associated with hereditary thrombophilia.